Russian Journal of Numerical Analysis and Mathematical Modelling (De Gruyter, 1986)
The journal provides English translations of selected new original Russian papers on the theoretical aspects of numerical analysis and the application of mathematical methods to simulation and modelling. The editorial board, consisting of the most prominent Russian scientists in numerical analysis and mathematical modelling, select papers on the basis of their high scientific standard, innovative approach and topical interest.